Human umbilical cord derived-mesenchymal stem cells alleviate lipid metabolism disturbances of hepatocytes via mitochondrial transport - Jing Xue; Xiangnan Hu; Suying Xia; Pengfei Ren; Aihong Wang (Gastroenterology & Endoscopy)
Objective: To explore the effect and mechanism of human umbilical cord derived-mesenchymal stem cells (UC-MSCs) on improving lipid metabolism disorders in vitro. Methods: Human liver cancer cell line HepG2 cells were divided into three groups: normal group, oleic acid treatment group (OA group), and OA ​+ ​MSCs group. Evaluate lipid deposition in HepG2 cells using oil red staining. Use a reagent kit to detect the triglyceride content in HepG2 cells. Evaluate the mitochondrial transport of MSCs to HepG2 cells using immunofluorescence staining and flow cytometry. Perform immunofluorescence staining to observe the formation of intercellular tunnel nanotubes (TNT). Evaluate the effect of UC-MSCs on HepG2 cells after the formation of TNT was inhibited by cytochalasin D (CytoD). Results: Compared with the OA group, the OA ​+ ​MSCs group showed a decrease in lipid deposition and triglyceride content in HepG2 cells. MitoTracker Red dye was used to label MSCs mitochondria, and flow cytometry showed that over 90 ​% of HepG2 cells had MitoTracker Red positive mitochondria, indicating a significant transfer of mitochondria from UC-MSCs to HepG2 cells. Immunofluorescence staining showed the formation of TNT structures between MSCs and HepG2 cells, and identified the transport of UC-MSCs mitochondria through TNT structures. After inhibiting TNT formation using CytoD, the effect of UC-MSCs on improving HepG2 lipid metabolism was weakened. Conclusion: UC-MSCs improve lipid metabolism in HepG2 cells through TNT mediated mitochondrial transport, indicating that mitochondria transfer-based therapies may be an innovative and promising therapeutic strategy for NAFLD.